Hubungan kepercayaan diri dengan kecemasan sosial pada remaja - Wardhana, Nadya Rizky Salsabila; Hudaniah; Sakinah Nur Rokhmah (Cognicia, 2024)
Navigating complex social situations can be challenging for adolescents who lead an active social life, potentially leading to social anxiety. Social anxiety can be overcome by having self-confidence. The purpose of this study is to determine the relationship between self-confidence and social anxiety in adolescents. The sample in this study with 213 teenagers from several regions in Indonesia, using the Simple Random Sampling. The design of the research used is a correlational design with Pearson correlation analysis techniques with SPSS version 25. The results of the study found that r= -0,206, p= 0,002 the meaning of significant negative relationship between self-confidence and social anxiety in adolescents, meaning that the higher the self-confidence it has, the lower the social anxiety experienced, and vice versa.